Estimating covariance matrices using estimating functions in nonparametric and semiparametric regression - Raymond J. Carroll; Stephen J. Iturria; Roberto G. Gutierrez (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
We use ideas from estimating function theory to derive new, simply computed consistent covariance matrix estimates in nonparametric regression and in a class of semiparametric problems. Unlike other estimates in the literature, ours do not require auxiliary or additional nonparametric regressions.
urn:nbn:de:kobv:11-10063741
Keywords: 330; Nonparametric regression; Estimating Equations; Kernel regression; Plug-in Semiparametrics; Smoothing